2012
DOI: 10.1080/14635240.2012.665581
|View full text |Cite
|
Sign up to set email alerts
|

Information seeking and use amongst people living with type 2 diabetes: an information continuum

Abstract: The purpose of this study was to examine the motives that people with type 2 diabetes (T2D) have in seeking information about their condition, and how information is used in self-care. Semi-structured interviews (N ¼ 25), focus groups (3 £ N ¼ 12 participants) and open-ended questionnaires (N ¼ 6) were used to collect qualitative data. Data were analysed thematically using framework analysis. In total, 37 participants took part, all recruited from a community-based diabetes participation group. The majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…People's motivations to look for and use health‐related information have been found to include receiving a diagnosis (Clark, ; Morgan & Trauth, ), as well as wanting to reduce negative effects, such as uncertainty, anxiety, and dread (Clark, ; Newton, Asimakopoulou, & Scambler, ); increase one's feeling of self‐efficacy (Clark, ); and regain a sense of control (Wong et al, ). With regard to information use , Newton, Asimakopoulou, and Scambler () found that people with type 2 diabetes are motivated to engage in self‐management activities out of a concern about the potential future negative physical effects of type 2 diabetes (particularly if they had observed such consequences happen to someone they knew), as well as a desire to stay well, maintain one's independence, reduce the need to consult healthcare professionals, and improve one's quality of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…People's motivations to look for and use health‐related information have been found to include receiving a diagnosis (Clark, ; Morgan & Trauth, ), as well as wanting to reduce negative effects, such as uncertainty, anxiety, and dread (Clark, ; Newton, Asimakopoulou, & Scambler, ); increase one's feeling of self‐efficacy (Clark, ); and regain a sense of control (Wong et al, ). With regard to information use , Newton, Asimakopoulou, and Scambler () found that people with type 2 diabetes are motivated to engage in self‐management activities out of a concern about the potential future negative physical effects of type 2 diabetes (particularly if they had observed such consequences happen to someone they knew), as well as a desire to stay well, maintain one's independence, reduce the need to consult healthcare professionals, and improve one's quality of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is no research in the United Kingdom to date to show that diabetes HCPs believe that patients’ knowledge is in any way ‘equivalent’ to theirs; that they believe that a consultation affirming empowerment ideals is the way forward for good diabetes control; or that they have the skills, aptitude and resources to move into empowering consultations. Professionals’ understandings of and attitudes towards empowerment in practice have been explored (Asimakopoulou et al, 2012; Newton et al, 2012; Scambler et al, 2012). This work suggests that there is little clarity or shared understanding about what empowerment is and what it involves and that there is disagreement about the degree of freedom that patients should have in making choices.…”
Section: Empowerment In the ‘Field’ Of Diabetesmentioning
confidence: 99%
“…Further, work conducted by us and others [ 10 , 27 29 ], respectively, shows that criteria for successful self-management differ amongst patients. Thus, we have a complex picture where there is great variability not only in the motives behind self-management, but also in how these motives shape criteria for assessing successful management and, hence, self-management styles.…”
Section: Discussionmentioning
confidence: 94%